PENAMAAN ANGGOTA PENCINTA ALAM - Muhammad Amirul Halim; Hadi Wardoyo ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
The naming of nature lovers is a unique phenomenon. They call it by the name of the field or the name of the jungle. However, for various reasons, not all nature lovers use the name jungle. This study aims to describe the background of the naming, the process of forming the name, and the sense of value that arises from the name. This study uses a type of qualitative approach. The data source for this research is students who are nature lovers in Malang. The data for this research are the names of the jungle members of nature lovers. The results of this study indicate that (1) the naming background can be shown through attitude, regional origin, and physical characteristics, (2) the process of forming is done by shortening or acronym and created by nature lovers themselves, (3) there are positive and negative taste values in each name.